Death & Data. - Bulger, Matthew (Humanist)
The author presents his thoughts on the U.S. Computer Fraud and Abuse Act (CFAA), which states that it is illegal to access websites without authorization. According to the author, the law does not clearly define "authorization" and often includes punishments that exceed the nature of the crimes. Particular attention is given to the case of computer programmer and activist Aaron Swartz who committed suicide in 2013 while under investigation for violating the CFAA